Tectonic and stratigraphic evolution of the Punta del Este and Pelotas basins (offshore Uruguay) - Morales, Ethel; Chang, Hung Kiang [UNESP]; Soto, Matias; Correa, Fernando Santos [UNESP]; Veroslavsky, Gerardo; Ana, Hector de Santa; Conti, Bruno; Daners, Gloria (Geological Soc Publ House, 2017)
Regional seismic reflection profiles and well data from the Uruguayan margin were integrated in order to analyse and illustrate its tectonic and stratigraphic evolution. The evolution of the Punta del Este and Pelotas basins is divided into four major phases: pre-rift (Palaeozoic); rift (Jurassic-Early Cretaceous); transition (Barremian-Aptian) and post-rift (AptianPresent). Each of these phases is characterized by a specific structural configuration and a stratigraphic architecture related to basin type, tectonic elements, sediment supply and base-level changes. During the geological evolution of the Uruguayan continental margin, a NE migration of depocentres occurred. The Cretaceous depocentre is located in the Punta del Este Basin, while the Cenozoic depocentre is located in the Pelotas Basin.